Scrutinizing the New Media and Religion Field of Study; History, Concepts and Theories With an Emphasis on Religious-Social Shaping of Technology - Hadi Khaniki; Amir Yazdian (مطالعات رسانه‌های نوین, 2021)
The first media religion studies dates back to 70s and 80s. Until the 1990s, this field had not been seriously considered by scholarships. Media studies’ affection by cultural studies and its apostasy (an important feature of cultural studies) are the main reasons for abandoning religion in media studies. Religious scholars also considered the mass media to be a factor in the weakening of religion, and therefore paid less attention to media studies. However, the emphasis of cultural approaches on the processes of meaning-making in society and the importance of religion as one of the most important components in the process of meaning-making of human agency caused attention to be turned to religion. Therefore, since the 90s, we have witnessed the growth of literature in the field of religion and media studies. Studies that began with the efforts of scholars such as Clifford Geertz and James Carey have continued up to the date and have grown due to the widespread influence of new media and their unique features at the community level. Examining the performance of religious groups, audience-oriented approach, examining religious news coverage, content analysis of religious topics, policy-making and critical content analysis have been among the main subjects of studies in this field, in recent years. However, the most important approaches to this emerging field of study can be found in Marshall McLuhan's "Technological Determinism"; Stig Hjarvard's "The Mediatization of Religion"; Stewart Hoover's "Mediation of Meaning"; Gordon Lynch’s "Mediation of Sacred Forms"; and Heidi Campbell’s "Religious-Social Shaping of Technology."